Bolivia's international relations at the beginning of the 21st century - Araníbar, Antonio (2016)
This article studies Bolivia's international relations from the 1990s until the present. Antonio Araníbar reflects upon the main topics of the Bolivian international agenda (neighbor policy, maritime reintegration, regional integration, and international cooperation on anti narcotic issues) and the Bolivian contribution to the region's multilateral agenda. The article concludes with a discussion of the priorities of Bolivia's foreign policy for the 21st century.